Pengaruh Mie Bayam Merah terhadap Peningkatan Kadar Hb untuk Remaja Putri - Ahmad Faridi; Taufik Maryusman; Ade Amalia; Mohammad Furqan (Jurnal Pustaka Padi (Pusat Akses Kajian Pangan dan Gizi), 2022)
Anemia is a medical problem that is most often found throughout the world, as well as being a major health problem for the community, especially in developing countries. The aim of the study was to assess the effect of red spinach noodles on increasing Hb levels for adolescents aged 15-17 years in Rawamangun Pelita Tiga SMAS. This research was conducted at Rawamangun Pelita Tiga High School involving female students aged 15-17 years with a sample of 30 people who had been screened first. The dependent variable studied was an increase in Hemoglobin levels, while the independent variables studied were the administration of red spinach noodles, macro nutrient intake, and iron intake. This type of research is quasi-experimental with sampling techniques using purposive sampling. The results of this study indicate that the majority of respondents had low hemoglobin levels before the intervention was given and there was an increase in hemoglobin levels after intervention, there was a significant difference between protein intake and fe intake to respondents before and after administration of red spinach noodles